Physiological and Biochemical Changes During Heat Stress Induced Browning of Detached Backhousia myrtifolia (Cinnamon Myrtle) Tissues - Sarana Sommano (2018)
© 2015, Springer Science+Business Media New York. Postharvest discolouration is found in leaf and floral tissues of Backhousia myrtifolia (Cinnamon myrtle). Towards discerning the biochemical mechanisms, heat-induced browning was investigated. Differential browning behaviour was observed for green versus yellowed leaves. Initial pre-treatment chlorophyll contents (Chl a and b) and chlorophyll fluorescence (CF) were measured for both coloured leaves. After heat treatment, both, coloured leaf and floral tissue, were analysed for electrolyte leakage (EL), malondialdehyde (MDA) content, polyphenol oxidase (PPO), peroxidase (POD) and phenylalanine ammonia lyase (PAL) enzyme activities, total phenolic content, diphenylpicryl-hydrazyl (DPPH) antioxidant activity and surface colour. They were also rated for their browning score (BS). Low chlorophyll fluorescence ratios (Fv/Fm values) of 0.68 for both leaf types suggested that this sub-tropical plant species experienced cold stress during winter period in which the study was conducted. Compared to detached green leaves, detached yellowed leaves showed more browning after heat treatment. Yellowed leaves had significantly greater EL levels, higher pre-treatment PPO and POX activities, and greater pre- and post-treatment PAL activities than green leaves. PPO, POD and PAL enzymes are typically involved in browning mechanisms in plant tissues. Their higher levels in yellowed leaves at least partly accounted for their greater browning than for green leaves.